Laminar convection heat transfer in square channel fitted diagonally with 45° V-discrete baffles - Tamna, Sombat; Poonperm, Rachan; Promvonge, Pongjet; Thianpong, Chinaruk (My University, 2014)
This work presents a numerical investigation of laminar periodic flow and heat transfer in a constant heat flux-surfaced square-channel fitted diagonally with 45° V-discrete baffles. The computations are based on the finite volume method, and the SIMPLE algorithm has been implemented. The fluid flow and heat transfer characteristics are presented for Reynolds numbers based on the hydraulic diameter of the channel ranging from 200 to 1,200. Effects of different blockage ratios (BR=b/H), BR in range from 0.05-0.2 with pitch ratio of 1.0 on heat transfer and pressure loss in the channel are studied. It is apparent that vortex flows created by the 45° diagonal V-discrete baffle exist and help to induce impinging flows on wall leading to drastic increase in heat transfer rate over the smooth channel. In addition, the increase in the BR results in the rise of Nusselt number and friction factor values. The computational results reveal that the optimum thermal enhancement factor of the 45° V-discrete baffle is about 2.24 at BR=0.2. © (2014) Trans Tech Publications, Switzerland.
Keywords: Heat transfer; Laminar flow; Periodic flow; Square channel; V-discrete